The Experience of Breast Cancer Undergoing Chemotherapy - Asti Melani Astari; Yati Sri Hayati; Dwi Intan Pakuwita AR; Kurnia Laksana (Universitas Aisyah Pringsewu, 2023)
Breast cancer is a disease that is still the biggest cause of death for women to date in developed and developing countries in the world. The World Health Organization stated that in 2017 there was an increase of a number of women diagnosed with breast cancer in Europe by a total of 250,000 cases. It means that every 28 hours there is a new case of a breast cancer diagnosis. The phases in the process of treating cancer patients require a certain series of activities. Throughout this continuum, individuals having breast cancer would be in experience physical and psychological changes, resulting in decreased quality of life. Clients with breast cancer need time to accept the condition of the pain so that it affects the follow-up treatment in the form of chemotherapy. This study uses a qualitative approach. In-depth interviews were conducted to explore participants' experiences deeper by analyzing data using Interpretative Analysis Phenomenology. This study results from seven themes namely (1) Family support as an encouragement to undergo chemotherapy (2) Accepting the disease process with anxiety (3) Tired of Chemotherapy (4) Hoping for healing through chemotherapy (5) Distrust of having breast cancer (6) Endeavor with the process alternative medicine (7) Surviving with Chemotherapy.